Non-Motor Aspects of Tic Disorders—New Developments - Ruhrman, Daphna; Gev, Ella; Benaroya-Milshtein, Noa; Fennig, Silvana; Krispin, Orit; Apter, Alan; Steinberg, Tamar (Frontiers in Psychiatry, 2017)
The cardinal characteristics of tic-related disorders are stereotyped motor movements and vocalizations. However, they may accompanied by non-motor features that appear sequentially during the course of the disorder and can sometimes be more disabling than the tics themselves. This review presents our perspectives on several non-motor aspects of Tourette syndrome based on the long experience of the Neuropsychiatric Tourette Clinic of a tertiary pediatric medical center. The effect of premonitory urges, sensory modulation disorder, tic-related cognitions, and environmental conditions on the expression and intensity of tics is elaborated, with suggestions for treatment approaches to each. We also describe the mediatory effect of parental attachment style on the link between maternal stress and ticcing intensity and the need to adjust psychotherapy interventions to account for the importance of this factor in emotion regulation. This review is intended to direct attention to the non-motor aspects of Tourette syndrome. An in-depth understanding of this complex and debilitating disorder will facilitate the formulation of innovative therapeutic protocols.